ON THE RESULTS OF THE ANALYSIS OF LEGISLATION OF THE REPUBLIC OF KAZAKHSTAN ON THE STATE REGISTRATION OF RIGHTS TO IMMOVABLE PROPERTY - Khassenov Муслим Ханатович (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2019)
This article presents the results of an analysis of the legislation of the Republic of Kazakhstan on state registration of rights to immovable property. Based on a study of strategic documents and legal doctrine, the author came to the conclusion that regulation of public relations in the field of state registration of rights to immovable property is aimed at the implementation of the strategic objectives of the Republic of Kazakhstan and the needs of civil relations. The author analyzed the Law of the Republic of Kazakhstan “On state registration of rights to immovable property” in order to identify contradictions between the norms of the Law and the norms of other laws, the availability of bylaws, corruption-related factors in the Law and the ineffectively implemented norms of the Law. In particular, collisions were revealed between the norms of the Law and the RK Civil Code, the RK Law “On credit bureaus and the formation of credit histories in the Republic of Kazakhstan”, the RK Law “On non-profit organizations”, RK Law “On rehabilitation and bankruptcy”. The absence of bylaws normative legal acts necessary for the implementation of this Law has been determined. In this regard, for the implementation of the Law, the authorized body has been recommended to develop and adopt relevant by-laws. In addition, there are examples of constitutional proceedings on the norms of this Law and their results. During the period of its validity, the norms of the Law (including those excluded from the Law) were twice the subject of constitutional proceedings to identify inconsistencies with the RK Constitution. It was pointed out a failure to implement the recommendation of the RK Constitutional Council on the need to adopt a separate Regulatory Resolution of the RK Supreme Court clarifying the procedure for applying legislation on state registration of rights to immovable property. As a result of the identified contradictions and shortcomings of certain norms of the Law, the author has developed proposals for amending and supplementing the RK legislation. стар әзірледі.